Generation and characterization of an inducible renal proximal tubule-specific CreERT2 mouse - Liang, Shiting; Wang, Youliang; Kang, Meixia; Deng, Juan; Chen, Liting; Hong, Xizhen; Hou, Fan Fan; Zhang, Fujian (Frontiers in Cell and Developmental Biology, 2023)
Protein reabsorption in renal proximal tubules is essential for maintaining nutrient homeostasis. Renal proximal tubule specific gene knockout is a powerful method to assess the function of genes involved in renal proximal tubule protein reabsorption. However, the lack of inducible renal proximal tubule specific Cre recombinase-expressing mouse strains hindered the study of gene function in renal proximal tubules. To facilitate the functional study of genes in renal proximal tubules, we developed an AMNCre-ERT2 knock-in mouse strain expressing a Cre-recombinase-estrogen receptor fusion protein under the control of the promoter of the amnionless (AMN) gene, a protein reabsorption receptor in renal proximal tubules. AMNCreERT2 knock-in mice were generated using the CRISPR/Cas9 strategy, and the tissue specificity of Cre activity was investigated using the Cre/loxP reporter system. We showed that the expression pattern of CreERT2-mEGFP in AMNCreERT2 mice was consistent with that of the endogenous AMN gene. Furthermore, we showed that the Cre activity in AMNCreERT2 knock-in mice was only detected in renal proximal tubules with high tamoxifen induction efficiency. As a proof-of-principle study, we demonstrated that renal proximal tubule-specific knockout of Exoc4 using AMNCreERT2 led to albumin accumulation in renal proximal tubular epithelial cells. The AMNCreERT2 mouse is a powerful tool for conditional gene knockout in renal proximal tubules and should offer useful insight into the physiological function of genes expressed in renal proximal tubules.